Kenny Ang, Aquinas and the biblical grounds of the doctrine of creation. An analysis of Thomas Aquinas’s Creation Theology in the Light of His References to Scripture, Roma: EDUSC, 2024, s. 375 - Roszak, Piotr (Studia Gdańskie, 2024)
Kenny Ang, Aquinas and the biblical grounds of the doctrine of creation. An analysis of Thomas Aquinas’s Creation Theology in the Light of His References to Scripture, Roma: EDUSC, 2024, s. 375